Topic controversies in the endoscopic management of malignant hilar strictures using metal stent: side‐by‐side versus stent‐in‐stent techniques. (1st July 2015) - Moon, Jong Ho; Rerknimitr, Rungsun; Kogure, Hirofumi; Nakai, Yousuke; Isayama, Hiroyuki
Abstract Endoscopic management of unresectable hilar malignant biliary stricture (MBS) is currently challenging, and the best approach is still controversial. Liver volume is the key to adequate biliary drainage in hilar MBS and multiple stenting is mandatory to drain over 50% of liver volume in most cases. The self‐expandable metallic stent (SEMS) has shown superior patency to plastic stents in recent reports. There are two methods of multiple stenting for hilar MBS: stent‐in‐stent (SIS) and side‐by‐side (SBS). Advantages of SIS include multiple SEMS placement in one stent caliber at the common bile duct (CBD), which is considered physiologically ideal. The through‐the‐mesh (TTM) technique with guidewires and the SEMS delivery system can be technically difficult in SIS, although the recent development of dedicated SEMSs having a loose portion facilitating the TTM technique makes SIS technically feasible both at stent deployment and re‐interventions. Conversely, the SBS technique, if placed across the papilla, is technically simple at initial placement and re‐intervention at stent occlusion. However, SBS has potential disadvantages of overexpansion of the CBD because of parallel placement of multiple SEMS, which can lead to portal vein thrombosis. Given the limited evidence available, a well‐designed randomized controlled trial comparing these two techniques is warranted.